INCIDENCE OF METALLO BETA-LACTAMASE PRODUCING PSEUDOMONAS AERUGINOSA IN CLINICAL SAMPLES - S. NAGAVENI, H. RAJESHWARI; OLI, AJAY KUMAR; S. A. PATIL; CHANDRAKANTH, R KELMANI (The Bioscan, 2010)
Metallo-beta-lactamases (MBLS) mediated resistance is an emerging threat in hospital isolates of Pseudomonas aeruginosa. The present study was undertaken to determine the incidence of MBL producing P. aeruginosa in clinical samples and to assess the clinical outcome after antimicrobial treatment. Of the 120 isolates of P. aeruginosa, 100% resistantce was found to five antibiotics i.e., ampicillin, ceftazidime, cefepime, ciprofloxacin and norfloxcin. Gentamycin showed 96% resistance. Resistance was moderate for tobramycin (44%) and was found to be low in case of amikacin (25%), 20% to carbenicillin and 32% to Imipenem. 50 (20.8%) were found to be MBL producers confirmed by disc potentiation method. The results of the present study demonstrate that the MBLproducing strains have significantly higher rates of resistance to β-lactam antibiotics.